Visible-Light-Driven Organic Photochemical Reactions in the Absence of External Photocatalysts - Wei, Yi; Zhou, Quan-Quan; Tan, Fen; Lu, Liang-Qiu; Xiao, Wen-Jing (Synthesis, 2019)
Visible-light-driven organic photochemical reactions have attracted substantial attention from the synthetic community. Typically, catalytic quantities of photosensitizers, such as transition metal complexes, organic dyes, or inorganic semiconductors, are necessary to absorb visible light and trigger subsequent organic transformations. Recently, in contrast to these photocatalytic processes, a variety of photocatalyst-free organic photochemical transformations have been exploited for the efficient formation of carbon–carbon and carbon–heteroatom bonds. In addition to not requiring additional photocatalysts, they employ low-energy visible light irradiation, have mild reaction conditions, and enable broad substrate diversity and functional group tolerance. This review will focus on a summary of representative work in this field in terms of different photoexcitation modes.1 Introduction2 Visible Light Photoexcitation of a Single Substrate3 Visible Light Photoexcitation of Reaction Intermediates4 Visible Light Photoexcitation of EDA Complexes between Substrates5 Visible Light Photoexcitation of EDA Complexes between Substrates and Reaction Intermediates6 Visible Light Photoexcitation of Products7 Conclusion and Outlook
Keywords: visible light; organic photochemical reactions; electron donor-acceptor complex; photoexcitation; free radicals